Participatory Variety Selection of Wheat, Barley, Broad Beans and Potato Combined with Double Cropping of Short Duration Crops - International Potato Center; International Maize and Wheat Improvement Center; International Center for Agricultural Research in the Dry Areas (International Food Policy Research Institute, 2015)
This data study contains data related to participatory variety selection (PVS) and double cropping of cereals, broad beans, and potato. Project title: Second Agreement Africa RISING (Research in Sustainable Intensification for the Next Generation: ILRI Contract No. ASSP-14/2014 Project abstract: The Ethiopian highlands are characterized by cereal-food legume production system where the productivity is very low due to pests, poor agronomic practices and growing of unimproved cultivars. Potato is becoming an integral parts of the production system of the highlands. Sustainability of cereals (wheat and barley) and potato is maintained through regular rotation with food legumes in small and main rainy seasons of the highlands. During the implementation of Africa RISING (AR) in Bale highlands and other projects, it was possible to identify high yielding cereal, broad beans and potato cultivars that can provide high yield and contribute to food security. However, many varieties are not tested in all the four AR sites. Moreover, there are early maturing legumes that can be used in double cropping with cereal and potato to increase land productivity in the highlands. Most of the wheat, barley, potato and broad beans cultivars released are developed with little or involvements of farmers and hence there is a need to put these varieties under PVS where farmers? inputs will be considered. Therefore, this study/intervention is designed to evaluate cultivars of the four commodities following PVS approaches as well as testing double cropping to increase land productivity. Project website: http://africa-rising.net